2021
DOI: 10.1016/j.resuscitation.2021.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal two years evaluation of neuropsychological outcome in children after out of hospital cardiac arrest

Abstract: Aim: To investigate longitudinal functional and neuropsychological outcomes 3-6 and 24 months after paediatric out-of-hospital cardiac arrest (OHCA). Further, to explore the association between pediatric cerebral performance category (PCPC) and intelligence.Methods: Prospective longitudinal single center study including children (0-17 years) with OHCA, admitted to the PICU of a tertiary care hospital between 2012 and 2017. Survivors were assessed during an outpatient multidisciplinary follow-up program 3-6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…Mean age ranged from 1.5 to 6.4 years. Three studies were conducted in the United States of America [ 22 , 23 , 24 ], two were conducted in the Netherlands [ 25 , 26 ], one in Finland [ 27 ], and one in Taiwan [ 28 ]. Two studies were prospective cohort studies, and five were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mean age ranged from 1.5 to 6.4 years. Three studies were conducted in the United States of America [ 22 , 23 , 24 ], two were conducted in the Netherlands [ 25 , 26 ], one in Finland [ 27 ], and one in Taiwan [ 28 ]. Two studies were prospective cohort studies, and five were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of survival beyond 1 year, only two [ 25 , 26 ] studies reported this outcome. Albrecht et al reported a survival of 95% at a median follow-up time of 26.3 months, while Hunfeld et al reported a survival of 98% at a mean follow-up time of 24 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations